Evaluation of a guideline for supportive anthroposophic therapies for hospitalised children with acute gastroenteritis - A prospective case series study - Melanie Schwermer; Katharina Fetz; Thomas Ostermann; Louisa Truxius; Alfred Längler; Tycho Jan Zuzak (Elsevier, 2024)
Objective: Even though several German children's hospitals offer integrative, anthroposophic medical therapies in addition to the standard medical care, guidelines for these anthroposophic therapies are still rare. Therefore, we investigated the feasibility of implementing a published, consensus-based guideline for the treatment of children with acute gastroenteritis (aGE) with anthroposophic therapies in the community hospital Herdecke. Design: A prospective case series of paediatric patients (≤18 years) with an aGE admitted to the department of integrative paediatrics of the community hospital Herdecke was conducted. Demographic, clinical and therapeutic data was recorded at initial presentation and at follow-up visits. Physicians were surveyed with a questionnaire to evaluate feasibility of implementing the guideline. Results: Sixty-two patients (0-15 years; 22 male, 40 female) were included in the case series. All patients received some form of anthroposophic therapy. The most frequently used remedies were Geum urbanum, Nux vomica and Bolus alba comp. Treating physicians showed a high adherence to the expert-based consensus guideline in their prescribed therapies. All physicians stated that they were familiar with the guideline and used the recommendation to inform their therapy decision. Suitability for daily use and effectiveness in treating the main symptoms of aGE were highly scored by the physicians. Conclusion: The consensus-based guideline of anthroposophic therapies for aGE in children was successfully implemented and found to be useful for physicians in clinical practice.